Vaccination in the immunotherapy of glioblastoma - Ziren Kong; Yu Wang; Wenbin Ma (Taylor & Francis Group, 2018)
Glioblastoma remains one of the most common central nervous system tumors with an extremely poor prognosis. Recently, rapid progress in immunotherapy has provided new options for the treatment of glioblastoma. Vaccination, the primary method of immunotherapy, stimulates the body's tumor-specific immune response by the injection of foreign antigens. Peptide vaccines involve the injection of tumor-specific antigens, such as EGFRvIII or heat-shock proteins. Cell-based vaccines, which primarily include dendritic cell vaccines and tumor cell vaccines, involve injections of ex vivo-modified cells. Despite the encouraging results of phase I/II clinical trials, no successful phase III clinical trials involving glioblastoma immunotherapy, including glioblastoma vaccinations, have been reported to date. In this review, the authors summarize the published outcomes of glioblastoma vaccine therapy, explore its future prospects based on ongoing clinical trials, and discuss combined therapy as a future direction for glioblastoma treatment.